Experimental investigation of the specific heat capacity of parent materials and composite adsorbents for adsorption heat pumps. (5th January 2020) - Rocky, Kaiser Ahmed; Islam, Md. Amirul; Pal, Animesh; Ghosh, Sampad; Thu, Kyaw; Nasruddin,; Saha, Bidyut Baran
Graphical abstract: Highlights: Cp of parent materials and consolidated composite adsorbents has been investigated. Experiments have been conducted at temperature ranging from 30 to 120 °C. Differential scanning calorimetry is employed to study the specific heat capacity. Tomeczek and Palugniok model is used to correlate the experimental Cp data. A generalized equation is proposed to calculate the Cp of any composite adsorbent. Abstract: Specific heat capacity (Cp ) of the adsorbents plays a vital role in the adsorption heat pump (AHP) systems design. This paper focuses on the experimental investigation of the Cp of parent materials and consolidated composite adsorbents at a temperature ranging from 30 to 120 °C. Here, the parent materials are highly porous adsorbent, namely Maxsorb III, thermal conductivity enhancers (TCEs) such as expanded graphites and graphene nanoplatelets, and binders, namely polyvinyl alcohol and polyvinylpyrrolidone. In addition, several consolidated composites are synthesized by varying the mass fraction of the adsorbent, TCE, and binder materials. Experimental Cp data of parent materials and composites are fitted with a widely used Tomeczek and Palugniok (TP) equation, and fittings show good agreements. Moreover, a generalized equation is proposed to calculate the Cp of composite adsorbents. Finally, experimental data of composites are fitted with the proposed equation, and the fittings show good agreements. These experimental data and the proposed equation are very crucial for the researchers to perform accurate AHP simulation, analysis, and compact system design.